Combustion synthesis of lead-free piezoelectric alkali metal niobate family - Chaiyo, Nopsiri; Muanghlua, Rangson; Wongprasert, Yothin; Seeharaj, Panpailin; Vittayakorn, Naratip (My University, 2013)
Nano-crystalline alkali metal niobate (ANbO3; A = K and Na) powders were synthesized by the combustion of nitrate compounds and Nb 2O5 using glycine as the fuel. The chemical reaction, nucleation mechanisms and influence of the fuel-to-oxidizer ratio to phase formation were studied. The precursor and product powders were characterized, using the thermo gravimetric analysis (TGA), Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD) technique, and scanning electron microscopy (SEM). Different fuel-to-oxidizer ratios were found to be a key factor of the process. As-prepared and calcined powders provided the perovskite structure with a nano-scale of mean crystalline size. © 2013 Copyright Taylor and Francis Group, LLC.